Intelligent Acting Digital Twins (IADT) - Ahcene Bounceur; Mostefa Kara (IEEE Access)
Digital twin technology has become a key enabler in modern system design and operation, allowing for real-time monitoring, simulation, and optimization. In this article, we present the Intelligent Acting Digital Twin (IADT), a concept that addresses a critical limitation of conventional digital twins, which are primarily passive tools for observation and simulation. The IADT introduces an active dimension by enabling digital twins to autonomously and adaptively control the physical counterpart. This is achieved through a reengineered system architecture that makes the physical system dynamically reprogrammable by the digital twin, ensuring seamless coordination and operational efficiency. The main contribution of the IADT lies in its ability to bridge the gap between virtual and physical systems, allowing for real-time decision-making and control in complex environments. For example, in a scenario involving a drone intercepting a virtual aircraft, the IADT functions as the central control unit, where real-time data and predictive models are used to autonomously guide the physical system. As proposed to traditional approaches, this bidirectional communication enhances adaptability, responsiveness, and overall system intelligence. The concept’s feasibility is validated through practical implementations using the CupCarbon simulator. These implementations demonstrate how the IADT integrates virtual and physical components to create a unified and effective framework, offering a significant advancement in the application of digital twin technology across various domains.